Short-Term Health Impact Assessment of Urban PM10 in Bejaia City (Algeria) - Fatima Benaissa; Cara Nichole Maesano; Rezak Alkama; Isabella Annesi-Maesano (Canadian Respiratory Journal)
We used Health Impact Assessment (HIA) to analyze the impact on a given population’s health outcomes in terms of all-causes mortality and respiratory and cardiovascular hospitalizations attributable to short-term exposure to particulate matter less than 10 μm diameter (PM10) in Bejaia city, for which health effects of air pollution have never been investigated. Two scenarios of PM10 reduction were considered: first, a scenario where the PM10 annual mean is decreased by 5 µg/m3, and then a scenario where this PM10 mean is decreased to 20 µg/m3 (World Health Organization annual air quality guideline (WHO-AQG)). Annual mean level of PM10 (81.7 µg/m3) was calculated from objective measurements assessed in situ. Each year, about 4 and 55 deaths could be postponed with the first and the second scenarios successfully. Furthermore, decreasing PM10 annual mean by 5 µg/m3 would avoid 5 and 3 respiratory and cardiac hospitalizations, respectively, and not exceeding the PM10 WHO-AQG (20 µg/m3) would result in a potential gain of 36 and 23 per 100000 respiratory and cardiac hospitalizations, respectively. Lowering in current levels of PM10 has a nonnegligible impact in terms of public health that it is expected to be higher in the case of long-term effects.